MEDIA COMPANY PROFILE SEBAGAI SARANA PENUNJANG INFORMASI DAN PROMOSI - Maimunah Maimunah; Lusyani Sunarya; Nina Larasati (CCIT Journal, 2012)
Currently, developments in information technology world and promoting media is growingrapidly, it is marked by numerous public needs that information. Types of supporting media campaign that is currently very varied, it was the demands of the promotional strategy developed by the company to achieve profit for the success of a company. Promotion is one determinant of the success of a marketing program within a company. Currently, media promotions such as anything that can provide information to the public or business entity that can communicate PT. Multi-Technology Innovation is good and interesting, to the audience so that the resulting information can be added value, sales value and whether it the name of the company, as one alternative to solving the problem, it needs a media campaign design an effective form of company profile, attract the attention of all consumers and for entrepreneurs to cooperate. The company profile you want to create it covers all the company’s assets include: History Company, Vision and Mission of the Company, Electronic Telephone Billing, Product Excellence, Regional Marketing, business models, corporate activities such as production, participation in exhibitions, collaborative activities withbusiness associates and others.